Pentacyclic Ingamine Alkaloids, a New Antiplasmodial Pharmacophore from the Marine Sponge Petrosid Ng5 Sp5 - Ilias, Muhammad; Ibrahim, Mohamed A.; Khan, Shabana I.; Jacob, Melissa R.; Tekwani, Babu L.; Walker, Larry A.; Samoylenko, Vladimir (Planta Medica, 2012)
Two new pentacyclic ingamine alkaloids, namely 22(S)-hydroxyingamine A (2) and dihydroingenamine D (3), together with the known ingamine A (1), have been isolated from marine sponge Petrosid Ng5 Sp5 (family Petrosiidae) obtained from the open repository of the National Cancer Institute, USA. The structures of compounds 1–3 were determined using 1D and 2D NMR, and HRESIMS techniques. The absolute configuration of both the C9 and C22 of 2 was determined as (S) using a modified Mosher esterification method. Compounds 1 and 3 showed strong antiplasmodial activity against chloroquine-sensitive (D6) and -resistant (W2) strains of Plasmodium falciparum with IC50 values of 90 and 78 ng/mL and 72 and 57 ng/mL, respectively, while 2 was found to be less active (IC50 values of 200 and 140 ng/mL, respectively). Compounds 1–3 were found to be devoid of in vitro cytotoxicity against human solid tumor cells of breast (BT-549), ovary (SK-OV-3), and epidermoid (KB) carcinomas and skin melanoma (SK-MEL), as well as against noncancerous monkey kidney fibroblasts (VERO) and pig kidney epithelial (LLC-PK11) cells, up to a maximum concentration of 10 µg/mL. Compounds 1–3 also displayed weak antimicrobial and moderate antileishmanial activities against Leishmania donovani promastigotes. These polycyclic ingamine alkaloids represent the first example of antiplasmodial leads without a β-carboline ring, which is known to be responsible for the cytotoxicity of the well-known manzamine class of marine alkaloids related to 1–3.
Keywords: Petrosid Ng5 Sp5; Petrosiidae; ingamine A; 22(S)-hydroxyingamine A; dihydroingenamine D; antiplasmodial